Rivers for life : managing water for people and nature - Postel, Sandra (Island Press, 2003)
Outlines plans to manage the world's rivers to restore some necessary functions of river ecosystems such as absorbing pollutants, decomposing waste, producing fresh water, and redistributing sediment to create animal habitats.